Study on Phalatrikadi Ghan Vati (Polyherbal formulation) As An Adjuvant In The Management of Thalassemia Major - Morey, Pavan; Sheshagiri, Srihari (International Journal of Psychosocial Rehabilitation, 2020)
Background: Thalassemia has not been described as a separate clinical entity in Ayurveda. The nearest possible correlation of Thalaseemia in Ayurveda can be with Pandu Roga(anaemic disorders). The prevalence of β-thalassemia patients in our india around 65,000-67,000 to 9,000-10,000 cases were added every year. Aim: The present study is aimed at evaluating the effect of PhalatrikadiGhanvati(polyherbal formulation) as an Adjuvant in the Management of Thalassemia Major and there by assessing the changes in the quality life. Material & Methods: The present study is designed as a randomized standard controlled clinical study, in which minimum of 15 patients will be enrolled in two groups. In Group A (Standard control) –Iron chelating therapy, Blood Transfusion will be administered and in Group B (Trial) –PalatrikadiGhanavatiwill be administered twice a day with warm waterafter meal for 60 days.Assessement will be recorded on 15th, 30th and 60th day. Results: Changes will be observed in subjective parameters such Daurbalya(Weakness)Aruchi(Anorexia)Udarshoola(Abdominal Pain) Sandhishoola (Joint Pain)Jwar (Fever) Panduta (Jaundice) Pleehavridhi (Spleenomegaly) Yakritvridh (Hepatomegaly) and objective parameters such as CBC with Peripheral smear, LFT, KFT,S. Iron, Total Iron Binding Capacity ( TIBC), S. Ferritin ,HB-Electrophorosis. Conclusion: Suitable conclusion will be drawn post completion of the trial.